Building Healthy and Sustainable Education Through Community Assistance - Sa'adah, Wazirotus; Ziyan, Salima; Zulkifi, Senjaya Machfudi; Sari, Ifit Novita (STAI Miftahul ULa Nganjuk, 2024)
The Kuliah Pengabdian Masyarakat Terintegrasi Kompetensi (KPM-IK) program in Desa Sidoharjo focuses on developing healthy and sustainable education. The primary aim of this initiative is to enhance the quality of education by integrating health aspects into the teaching and learning process. The program utilizes the Asset-Based Community Development (ABCD) approach, which involves the community in identifying local resources to promote healthy lifestyles and integrate health education into the local curriculum. The program's activities include health education outreach, physical activities, and promoting healthy living habits. The results demonstrate a significant improvement in the community’s understanding of the importance of health in education, as well as increased participation in physical activities and healthier lifestyles. This initiative successfully highlighted the interconnection between education and health, leading to a more holistic approach to community development